Spatially Conditioned Speech Timing: Evidence and Implications - Shaw, Jason A.; Chen, Wei-rong (Frontiers in Psychology, 2019)
Patterns of relative timing between consonants and vowels appear to be conditioned in part by phonological structure, such as syllables, a finding captured naturally by the two-level feedforward model of Articulatory Phonology (AP). In AP, phonological form – gestures and the coordination relations between them – receive an invariant description at the inter-gestural level. The inter-articulator level actuates gestures, receiving activation from the inter-gestural level and resolving competing demands on articulators. Within this architecture, the inter-gestural level is blind to the location of articulators in space. A key prediction is that intergestural timing is stable across variation in the spatial position of articulators. We tested this prediction by conducting an Electromagnetic Articulography (EMA) study of Mandarin speakers producing CV monosyllables, consisting of labial consonants and back vowels in isolation. Across observed variation in the spatial position of the tongue body before each syllable, we investigated whether inter-gestural timing between the lips, for the consonant, and the tongue body, for the vowel, remained stable, as is predicted by feedforward control, or whether timing varied with the spatial position of the tongue at the onset of movement. Results indicated a correlation between the initial position of the tongue gesture for the vowel and C-V timing, indicating that inter-gestural timing is sensitive to the position of the articulators, possibly relying on somatosensory feedback. Implications of these results and possible accounts within the Articulatory Phonology framework are discussed.